2016
DOI: 10.3390/toxins8120347
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of Aflatoxin M1 Contamination and Poorer Composition of Milk Supplied by Informal Milk Marketing Chains in Pakistan

Abstract: The present study was conducted to observe the seasonal variation in aflatoxin M1 and nutritional quality of milk along informal marketing chains. Milk samples (485) were collected from three different chains over a period of one year. The average concentrations of aflatoxin M1 during the autumn and monsoon seasons (2.60 and 2.59 ppb) were found to be significantly higher (standard error of the difference, SED = 0.21: p = 0.003) than in the summer (1.93 ppb). The percentage of added water in milk was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
1
6
3
Order By: Relevance
“…The present study results are in exact agreement with previous studies conducted in Pakistan [15,22,27,31,35,56], where they reported higher contamination of milk with AFM 1 in the winter season. The present study found high levels of AFM 1 contamination in milk samples collected in the autumn season (0.751 μg/L) after winter (0.875 μg/L); hence, the results are in agreement with those of Aslam, et al [57], who reported significantly higher AFM 1 levels in milk during the autumn season (2.60 μg/L). Similar studies conducted by Hojjatollah and Sepideh [58] also reported an increased level of AFM 1 contamination in milk during the winter and autumn seasons, with an average value of 54.24 and 34.92 ng/L, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The present study results are in exact agreement with previous studies conducted in Pakistan [15,22,27,31,35,56], where they reported higher contamination of milk with AFM 1 in the winter season. The present study found high levels of AFM 1 contamination in milk samples collected in the autumn season (0.751 μg/L) after winter (0.875 μg/L); hence, the results are in agreement with those of Aslam, et al [57], who reported significantly higher AFM 1 levels in milk during the autumn season (2.60 μg/L). Similar studies conducted by Hojjatollah and Sepideh [58] also reported an increased level of AFM 1 contamination in milk during the winter and autumn seasons, with an average value of 54.24 and 34.92 ng/L, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In the latter study, only 3% samples were found to exceed the 500 ng of AFM 1 /L limit, while the former two authors did not find any sample to exceed this limit. Contrary to these studies, Aslam et al (2016) found 87% of milk samples to exceed the 500 ng/L limit in three districts of Punjab province. Likewise, Akbar et al (2019) found 69% milk samples from different regions of the Punjab province to exceed the allowed limit.…”
Section: Introductioncontrasting
confidence: 79%
“…In 2011, Fallah et al disclosed 323 ng/kg as the mean value of aflatoxin M1 in Iran [ 42 ] whereas in 2018, Asghar et al from Pakistan reported 346.2 ng/kg as mean aflatoxin M1 level in 91.7% fresh milk samples [ 43 ]. In 2016, Aslam et al reported presence of aflatoxin M1 in each and every 468 fresh milk samples where 2600 ng/kg was the mean level [ 44 ]. Though occurrence of AFM1 contamination is remarkable in South Asian countries rather than European ones as they possess stringent laws and good storage practices of feedstuffs to control aflatoxins [ 41 ], the present results show lower contamination of AFM1 than some other European countries like Greece and Portugal where up to 90% of aflatoxin M1 presence was noticed in raw milk [ 45 , 46 ] respectively.…”
Section: Resultsmentioning
confidence: 99%